The evaluation of different types fecal bacteria products for the treatment of recurrent Clostridium difficile associated diarrhea: A systematic review and network meta-analysis - Yang, Liping; Li, Wenrui; Zhang, Xianzhuo; Tian, Jinhui; Ma, Xiaojia; Han, Lulu; Wei, Huaping; Meng, Wenbo (Frontiers in Surgery, 2022)
Purpose To determine the efficacy of different types of fecal microbiota transplantation for the treatment of recurrent clostridium difficile associated diarrhea (RCDAD). Methods We searched PubMed, Embase, The Cochrane Library, Web of Science, China Biomedical Medicine (CBM), China National Knowledge Infrastructure (CNKI) and WanFang database. We also tracked the references found in systematic reviews of RCDAD treated with fecal microbiota transplantation. We included randomized controlled trials (RCTs) comparing different types of fecal microbiota transplantation with other methods for the treatment of RCDAD. The search period was from the date of inception of this treatment method to January 16, 2022. Two reviewers independently screened the published literature, extracted the data and assessed the risk of bias. Systematic review and network meta-analysis were conducted using RevMan 5.4, Stata 16.0 and R 4.1.2 software. Results Ten RCTs involving 765 patients were included in this network meta-analysis. The results showed that treatment with fresh fecal bacteria and frozen fecal bacteria were better than vancomycin, fresh vs. vancomycin [odds ratio, (OR) = 8.98, 95% confidence interval (95% CI) (1.84, 43.92)], frozen vs. vancomycin [OR = 7.44, 95% CI (1.39, 39.75)]. However, there were no statistically significant differences in cure rate [fresh vs. frozen: OR = 1.21, 95% CI (0.22, 6.77); fresh vs. lyophilized, OR = 1.95, 95% CI (0.20, 19.44); frozen vs. lyophilized, OR = 1.62, 95% CI (0.30, 8.85)]. The Surface Under the Cumulative Ranking (SUCRA) indicated that fresh fecal bacteria were the best treatment for RCDAD. Conclusions Fresh fecal bacteria are the best treatment of RCDAD, frozen fecal bacteria and lyophilized fecal bacteria can achieve the same effect. Fecal microbiota transplantation is worthy of clinical and commercial application.